Bani Israil in the Qur’an and Modern Israel: Symbolic Continuity and Political Discontinuity of Jewish Identity - Alfian Yahya; Muhammad Sufiyan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This article aims to analyze the relationship between Bani Israil in the Qur’an and modern Israel by proposing the framework of symbolic continuity and political discontinuity of Jewish identity. The study arises from the tendency in contemporary religious and media discourse to conflate Bani Israil, Jews, Zionism, and the State of Israel into a single identity. Such conflation presents an academic problem because the Qur’an uses the term Bani Israil in a historical-religious context related to the descendants of Prophet Ya‘qub, prophetic experiences, divine covenants, transgressions, and moral admonitions. In contrast, modern Israel is a nation-state formed through Jewish nationalism, political Zionism, colonialism, the British mandate, and twentieth-century geopolitical configurations. This research employs a qualitative library-based method with a historical-genealogical approach. The primary data consist of Qur’anic verses concerning Bani Israil, Jews, Hādū, and Ahl al-Kitāb, while supporting data include tafsir literature, Jewish history, Zionism, modern Israel, identity theory, and relevant contemporary media. The study finds that modern Israel cannot be directly identified with Qur’anic Bani Israil because they differ in political structure and historical context. However, modern Israel is not entirely disconnected from Jewish tradition, as it employs names, symbols, territorial memory, and genealogical narratives to legitimize its national identity. Thus, the relationship between the two is best understood as symbolic continuity alongside political discontinuity. This article contributes to Qur’anic and Jewish identity studies by formulating symbolic continuity and political discontinuity as a proportional framework that distinguishes Qur’anic moral-genealogical categories from modern nationalist and legal-political constructions of Israel.